Contexto climático y parámetros meteorológicos en la ciudad de Bahía de Caráquez, Manabí - Ecuador - Macías Pisco, Nachy Monserrat (2025)
The general objective of the research was to evaluate the climatic context and meteorological parameters in Bahía de Caráquez, Manabí Province – Ecuador, in order to identify trends, establish correlations, and project climatic scenarios to design prevention, mitigation, and adaptation strategies against climate change. The applied methodology was quantitative, descriptive, and correlational, using historical temperature and precipitation series (1981–2024) from the NASA POWER database, complemented with local data obtained through a Sainlogic WS300 automatic weather station between September 2024 and July 2025. Inductive–deductive, statistical, and comparative methods were employed, supported by observation, literature review, correlational analysis using Pearson’s coefficient, and climate projections via linear regression, as well as climatic classification using the Whittaker diagram. The results showed that Bahía de Caráquez has a dry tropical climate, with a progressive increase in temperature and variability in rainfall. Correlations between meteorological parameters were weak to moderate: temperature-humidity (r = 0.38), temperature-precipitation (r = 0.37), temperature-pressure (r = -0.77), and precipitation-humidity (r = -0.08). Climate projections suggest warmer and more irregular scenarios toward the end of the 21st century. The city’s climatic dynamics respond to local, regional, and global factors, increasing its vulnerability. In this context, the proposed strategy guide represents a contribution to strengthening community resilience through environmental education, reforestation, rainwater harvesting, land-use planning, and early warning systems, contributing to effective adaptation to climate change.